110k views
0 votes
Which statement best explains the value of 17 − (−3)? (10 point)

The additive inverse of −3 is −3, so 17 − (−3) = 14.

The additive inverse of −3 is −3, so 17 − (−3) = 20.

The additive inverse of −3 is +3, so 17 − (−3) = 20.

The additive inverse of −3 is +3, so 17 − (−3) = 14.

2 Answers

2 votes

Answer:

17-(-3) = 20.

Explanation:

17-(-3) = 17 + 3 = 20.

This is true because a minus sign before a set of parentheses changes the sign within the parenthesis to the opposite. Therefore, -3 would be +3.

User Colin Sygiel
by
6.4k points
4 votes

Answer:

C) The additive inverse of −3 is +3, so 17 − (−3) = 20.

Explanation: